Meningkatkan Kemampuan Bernalar kritis dan Hasil Belajar Siswa Melalui Pendekatan PBL pada Pendidikan Agama Katolik - Mercurius Dwi Ismarwanto; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The background of this classroom action research is: 1) the low critical reasoning ability of students as seen by the lack of active participation in discussions, 2) the lack of ability to analyze problems and argue logically, and 3) low learning outcomes in Catholic Religious Education (PAK) learning. So far, the learning approach applied by teachers still uses a lecture or monologue approach. This research aims to: 1) improve students' critical reasoning skills through active participation in discussions in PAK lessons through the Problem Based Learning (PBL) approach, 2) improve students' ability to analyze problems and argue logically, and 3) improve student learning outcomes in Catholic Religious Education (PAK) learning. To overcome this challenge, interesting learning methods are needed to increase teaching outcomes and student interest in the classroom. One method that has proven effective is Problem Based Learning (PBL). Focusing on the critical reasoning dimension of the Pancasila Student Profile is intended to improve the affective aspect in the learning process. The research process was carried out for 2 cycles which were divided into stages: 1) Planning; 2) Implementation; 3) Observation; 4) Reflection. The respondents of this study were 13 students consisting of 9 male students and 4 female students. The results showed that the critical reasoning aspect increased by 26.2%, from cycle 1 with 60% and cycle 2 to 86.2%. Meanwhile, the results of the cognitive aspect test in cycle 1 of the Jesus material proclaiming the Kingdom of God with an average score of 62 increased to 85 in cycle 2 with the material The Passion and death of Jesus. The results of the reflection recommend that there needs to be assistance in the affective aspect for students so that it can improve student learning outcomes. Thus, learning with the PBL approach by focusing on one dimension of critical reasoning can significantly improve student learning outcomes.